2018
DOI: 10.1016/j.cardfail.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Contraction Fraction by M-Mode Echocardiography Is Superior to Ejection Fraction in Predicting Mortality in Transthyretin Amyloidosis

Abstract: NCT00628745.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 56 publications
1
48
0
1
Order By: Relevance
“…Myocardial contraction fraction (MCF), which indexed the SV to the myocardial volume, was calculated as previously described. 24 Disproportionate hypertrophy was defined as an IVSd greater than 1.9 cm in males or 1.6 cm in females. ‘Classical’ low-flow, low-gradient was defined as an aortic valve area ≤1.0 cm 2 , with an LVEF <50%, an indexed SV <35 mL/m 2 , a peak aortic valve velocity <4 m/s, and a mean gradient <40 mmHg, conversely ‘paradoxical’ low-flow, low-gradient was defined as an LVEF ≥50%, but an indexed SV <35 mL/m 2 , peak velocity <4 m/s, and mean gradient <40 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…Myocardial contraction fraction (MCF), which indexed the SV to the myocardial volume, was calculated as previously described. 24 Disproportionate hypertrophy was defined as an IVSd greater than 1.9 cm in males or 1.6 cm in females. ‘Classical’ low-flow, low-gradient was defined as an aortic valve area ≤1.0 cm 2 , with an LVEF <50%, an indexed SV <35 mL/m 2 , a peak aortic valve velocity <4 m/s, and a mean gradient <40 mmHg, conversely ‘paradoxical’ low-flow, low-gradient was defined as an LVEF ≥50%, but an indexed SV <35 mL/m 2 , peak velocity <4 m/s, and mean gradient <40 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…The deposit of those proteins disrupts the structure and function of the heart with a thickening of the ventricular wall, an increase of the myocardial mass and a reduction in end-diastolic volume leading to a diastolic dysfunction, an impaired myocardial contraction, and a progressive heart failure and death. [1][2][3] Untreated, CA is life threatening from few months for AL to few years for ATTR. [4][5][6] Consequently, identifying patients with a poor prognosis is fundamental to ensure adequate treatment and a timely referral to specialised centres.…”
Section: Introductionmentioning
confidence: 99%
“…In another major study cohort, the Multi-Ethnic Study of Atherosclerosis, Abdalla et al also reported that the lowest MCF quartiles was associated with an increased risk for incident CVD (myocardial infarction, resuscitated cardiac arrest, stroke, coronary heart disease and stroke death) (HR: 2.42, 95%CI: 1.58-3.72) 18 . In patients with cardiomyopathy, including cardiac amyloidosis and non-ischemic cardiomyopathy, historical studies consistently confirmed the prognostic capacity for adverse outcomes [9][10][11] . Few data have evaluated the role of MCF played in patients with HCM.…”
Section: Discussionmentioning
confidence: 84%